2013
DOI: 10.1007/s10549-013-2592-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of progesterone receptor gene (PGR) variants and breast cancer risk in African American women

Abstract: Background Prolonged exposure to combined hormone replacement therapy (estrogen plus progestin) increases a woman’s risk of breast cancer whereas estrogen-only hormone replacement therapy does not. This suggests that progesterone may play a role in breast carcinogenesis. Association studies have reported inconsistent relationships between progesterone receptor gene variants and breast cancer. Methods A population- based case-control study in three counties of the Philadelphia Metropolitan area was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Multiple studies have reported breast cancer associations with PGR SNP rs1042838 [6871], but a later, larger meta-analysis showed no association [72]. Breast cancer associations have also been reported in a small AA sample for rs590688 and rs10895054 [73]. These three SNPs were not associated with breast cancer in the present study.…”
Section: Discussioncontrasting
confidence: 48%
“…Multiple studies have reported breast cancer associations with PGR SNP rs1042838 [6871], but a later, larger meta-analysis showed no association [72]. Breast cancer associations have also been reported in a small AA sample for rs590688 and rs10895054 [73]. These three SNPs were not associated with breast cancer in the present study.…”
Section: Discussioncontrasting
confidence: 48%
“…Rs11224565 is a noncoding variant located in the 3'UTR and could potentially influence BMI via alterations in gene expression [40,46]. Prior work has shown that rs10895054 is associated with increased risk of breast cancer in African American women [47]. BMI at age 10 is inversely associated with breast cancer risk in premenopausal women [48].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in tumor biology and genetic variances might explain the racial disparities in our study. Black Americans with breast cancer were reported to have differences in progesterone receptor genes [ 26 ]. Such differences could also exist in thyroid cancer between white and black Americans.…”
Section: Discussionmentioning
confidence: 99%